2022
DOI: 10.3390/ph15101236
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dots for Killing Microorganisms: An Update since 2019

Abstract: Frequent bacterial/fungal infections and occurrence of antibiotic resistance pose increasing threats to the public and thus require the development of new antibacterial/antifungal agents and strategies. Carbon dots (CDs) have been well demonstrated to be promising and potent antimicrobial nanomaterials and serve as potential alternatives to conventional antibiotics. In recent years, great efforts have been made by many researchers to develop new carbon dot-based antimicrobial agents to combat microbial infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 109 publications
0
6
0
Order By: Relevance
“…One of the techniques is doping with heteroatoms such as boron, sulfur, nitrogen, iodine, etc (36,38). Another method includes conjugating CDs with metals such as gold (39) and using both toxic and non-toxic chemicals as precursors for synthesizing antifungal CDs (51)(52)(53). However, most tests have used high concentration of drugs and have only performed short term cytotoxic assays.…”
Section: Discussionmentioning
confidence: 99%
“…One of the techniques is doping with heteroatoms such as boron, sulfur, nitrogen, iodine, etc (36,38). Another method includes conjugating CDs with metals such as gold (39) and using both toxic and non-toxic chemicals as precursors for synthesizing antifungal CDs (51)(52)(53). However, most tests have used high concentration of drugs and have only performed short term cytotoxic assays.…”
Section: Discussionmentioning
confidence: 99%
“…The oxygenous characteristic of carbon quantum dots makes covalent bonding with functionalizing chemicals possible. CQDs have numerous applications in industrial fields [34] due to their enormous surface area, high electric conductivity, and quick electric charge transfer, as well as high physiochemical properties including crystallization, dispersibility in different liquids, and photoluminescence. In particular, the small size, superconductivity, and rapid electron transfer of CQDs endow the CQDs-based composites with improved electric conductivity and catalytic activity.…”
Section: P-cqdsmentioning
confidence: 99%
“…The CQDs were reported to have medicinal therapeutic effects [ 15 , 16 , 24 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. It was indicated that all these biomass-derived CQDs contain the nitrogen element, which might be from the proteins, amino acids, and nucleic acids in the biomass [ 34 ]. Furthermore, metal-containing CQDs ( Figure 3 ) are divided into four types that can be used as antimicrobial agents: metal ion-doped CQDs, metal nanoparticle-decorated CQDs, CD/metal oxide nanocomposites, and CQD/metal sulfide nanocomposites [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Carbon dots (CDs) are carbon-based nanoparticles with diameters of 2–10 nm that possess functionalized surfaces. CDs have numerous advantages over other nanoparticle classes because of their easy preparation, stable fluorescence, and good water stability and biocompatibility. , CDs have been used in the biomedical field as carriers of pharmacologic drugs and antibacterial agents. For instance, CDs synthesized from p -phenylenediamine and polyethylenimine can effectively reduce wound infections caused by Staphylococcus aureus . CDs were also able to overcome the photoinstability of curcumin, and curcumin-loaded CDs enhanced reactive oxygen species (ROS) generation via fluorescence resonance energy transfer to achieve efficient antibacterial activity .…”
Section: Introductionmentioning
confidence: 99%